Answer:
-1.25
Step-by-step explanation:
t÷3-1÷2 = t÷1+3÷9
2t-3÷6 = 9t+3=9
18t - 27 = 54 + 18
18t -54t = 18 + 27
-36t = 45
Divide through by -36
t = -1.25
Answer:
36=b^2 or b=the square root of 36
Step-by-step explanation:
The sides of a square are all equal in length. To find the area of a square you can multiply the two sides together. Considering that they are the same length, you can just square one of the side lengths to get your answer. To find a side length you can take the square root of the area.
Answer:
Step-by-step explanation:
b · b = 36
Answer:
a
Step-by-step explanation:
Multiples of 15: 15, 30, 45, 60, . . .
The least common multiple is 60.
What is Maria’s error?
the answer is IDK
Answer:
The Least Common Multiple is 3
Step-by-step explanation:
Maria's error was that she tried finding the largest multiple rather than the least.
Answer:
Step-by-step explanation:
Maria's error on this is the LCM is 30 not 60
the least is 30 not 60
Answer:
49 days
Step-by-step explanation:
The spread of the disease is modeled as
where n = number of infected people
t = time (in days)
When the number of infected people is 1400, the number of days t will be:
It will take 49 days for the number of infected people to reach 1400.
Given the function n=200 Square root t where n is the number of infected, and t is time, it will take 49 days for the number of infected people to reach 1400.
To find out how long it will take until the number of infected people reaches 1400, we are going to set n = 1400 (number of infected people) in the given equation, and then solve for t (time in days).
So, 1400 = 200 √t. Dividing both sides by 200, we get √t = 7. Then, squaring both sides give us t = 49 days. So, it will take 49 days for the number of infected people to reach 1400.
Given the function n=200 Square root t where n is the number of infected, and t is time, it will take 49 days for the number of infected people to reach 1400.
#SPJ3
Given:
The statement is "the difference of 18 and 12".
To find:
The expression for the given statement.
Solution:
We have,
Given statement = The difference of 18 and 12.
We use subtraction, to find the different between two numbers and subtraction is represented by negative sign. So, we need to subtract second number form the first number.
The difference of 18 and 12 = 18 - 12
Therefore, the required expression for the given statement is 18-12.